ROLE OF LAW IN CONSTRUCTION AND DEVELOPMENT OF SMALL SCALE INDUSTRIES THROUGH NORMATIVE PERSPECTIVE - Endang Sutrisno (Faculty of Law, Universitas Jenderal Soedirman, 2015)
The presence of law has become an absolute prerequisite that must exist in the dynamics of civil society. It is to achieve justice, certainty, and expediency, so the works of it will not be separated from such a noble mission. On the other side, the law is likely inseparable from the fields of meta-juridical, including economics. The expectations of the interference of law into economy, makes the existence of justice for the business players can be realized through the enacted product legislation. Regulations concerning investments and partnerships have the intent to build self-reliance and empowerment for small industry players so as to compete in the era of economic globalization. Laws employed as the instrument of social change to strengthen the capitalization of small industry and business empowerment through the training and development of small industries, as normatively mandated by law. Key words : Law, Economic, Small Industry